PS, It’s Complicated: The Roles of Phosphatidylserine and Phosphatidylethanolamine in the Pathogenesis of Candida albicans and Other Microbial Pathogens - Chelsi D. Cassilly; Todd B. Reynolds (Journal of Fungi, 2018)
The phospholipids phosphatidylserine (PS) and phosphatidylethanolamine (PE) play important roles in the virulence of Candida albicans and loss of PS synthesis or synthesis of PE from PS (PS decarboxylase) severely compromises virulence in C. albicans in a mouse model of systemic candidiasis. This review discusses synthesis of PE and PS in C. albicans and mechanisms by which these lipids impact virulence in this fungus. This is further compared to how PS and PE synthesis impact virulence in other fungi, parasites and bacteria. Furthermore, the impact of PS asymmetry on virulence and extracellular vesicle formation in several microbes is reviewed. Finally, the potential for PS and PE synthases as drug targets in these various kingdoms is also examined.